EPISTEMOLOGICAL MANAGEMENT IN ISLAMIC EDUCATION INNOVATION: STRATEGIES FOR QUALITY ENHANCEMENT BASED ON THE DIGITAL ECOSYSTEM - Muhammad Afifudin; Sukarman Sukarman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This research aims to formulate an epistemological foundation for innovation in Islamic education management and actualize it into quality improvement strategies responsive to the challenges of digital transformation. This study employs a qualitative approach using a descriptive-analytical library research method. Primary data sources rely on articles from reputable national and international scientific journals. The collected data were examined using content analysis techniques and critical interpretation , validated to ensure credibility through source triangulation mechanisms and confirmability testing. The main findings conclude that digital transformation in Islamic education requires the reconstruction of management epistemology that fully integrates rational technological advancement with divine values. The digital ecosystem and Management Information Systems (MIS) must not be viewed as the ultimate goal, but purely as strategic instruments to boost academic service quality and shape students' characters holistically. The successful integration of digital governance heavily relies on organizational cultural readiness and digital literacy skills, supported by transformational leadership based on prophetic values. Without these strong cultural foundations and leadership capacities, technology adoption will only result in symbolic administrative modernization detached from the Islamic spirit, failing to provide essential quality improvements.